Role of Information Systems and Mobile Technology in Optimizing Organizational Learning Effectiveness - Dhaou, Fatma; Abdo, Khalid Waleed Ahmed; Aljehani, Sultan; Hidayat-ur-Rehman, Imdadullah; Mohamed Ibrahim Badran, Doaa; Abdelhady, Mahmoud (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The main purpose of this work is to understand the role of information systems (IS) and mobile technologies (MT) in improving the effectiveness of organizational learning (OL). Increasingly, organizations are changing their learning paradigms to incorporate new technologies, which is the focus of this study. This study is primarily qualitative and uses a mixed-methods approach. In the first of the two phases of the study, a systematic literature review (SLR) was used, and in the second phase, a bibliometric review was conducted using the software VOSviewer. To contextualize and understand current practices, the researcher conducted interviews with senior executives in both the public and private sectors, i.e., multinational and national organizations. The findings of this study reveal that IS and MT impact the effectiveness of OL by facilitating the flow of knowledge and the accessibility of learning materials, as well as improving collaboration within an organization. The bibliometric review demonstrated the importance, themes, and emerging trends of such technologies in the field of modern organizational learning. The qualitative study also confirmed that IS and MT foster a culture of continuous learning and development. The study applied a mixed-methods approach to uncover the role of IS and MT in the organizational learning effectiveness (OLE) and found that IS and MT play a role in streamlining knowledge-sharing processes, enhancing accessibility to educational resources, and fostering organizational collaboration.